2014
DOI: 10.3390/insects5040942
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Various Natural or “Green” Insecticides against Bed Bugs: A Double-Blind Study

Abstract: Bed bugs are resurging throughout the world, and, thus, effective pest control strategies are constantly needed. A few studies have evaluated 25(b) and other natural, or so-called “green” products, as well as over-the-counter insecticides for bed bugs, but additional studies are needed to determine efficacy of bed bug control products. This double-blinded research project was initiated to examine long-term effectiveness of six commercially available natural or “green” insecticides against bed bugs and to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In our study, short exposure of bed bugs to DE and Alpine caused low mortality (<36.7%), confirming that brief contact of insects with DE-based products have limited lethal effect. Moreover, one-day exposure to a surface treated with DE or Alpine caused similar low mortality in bed bugs [ 43 ]. In this later study, mortality was recorded for only 48 h after exposure, a limited time to observe the insecticidal effects of these products.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, short exposure of bed bugs to DE and Alpine caused low mortality (<36.7%), confirming that brief contact of insects with DE-based products have limited lethal effect. Moreover, one-day exposure to a surface treated with DE or Alpine caused similar low mortality in bed bugs [ 43 ]. In this later study, mortality was recorded for only 48 h after exposure, a limited time to observe the insecticidal effects of these products.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the recent emergence of neonicotinoid resistance in the United States [8] or, as the authors suggest, the consequence of a generally scattered bed bug distribution as a result of resident’s relocating infested belongings. However, a second study examining 6-month aged residues of Alpine Dust Insecticide found the product resulted in only 40% mortality when tested against susceptible C. lectularius , and negligible mortality against resistant C. lectularius , further suggesting this product should only be included as part of a completely integrated program of other control methods for long-term reduction or control against modern field strains of bed bugs [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Both forms of desiccant dust possess discernable efficacy against bed bugs [24,41,42,43,44,45,46,47] although results have been variable depending on the product tested and bed bug strain(s) used. Diatomaceous earth has been found to be effective, under laboratory conditions, at application rates between 1–8 g/m 2 , achieving 100% mortality against adults over the course of 9–15 days and 99% mortality against nymphs after 2 days [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thymol was reported as having repellent activity against Blatella lateralis (Walker) (Blattodea: Blattidae) [ 24 ]. In bed bugs, several studies have evaluated the contact toxicity [ 27 , 28 , 29 , 30 , 31 ], fumigant toxicity [ 29 , 32 , 33 ], and residual toxicity [ 34 , 35 ] of plant-derived pesticides, but few have studied in detailed their repellency. Anderson et al [ 36 ] demonstrated the efficacy of three naturally occurring repellents, para-menthane-3,8-diol, delta dodecalactone, and gamma dodecalactone to prevent bed bugs from hiding in substrate-treated areas.…”
Section: Introductionmentioning
confidence: 99%